THE EFFECT OF ISLAMIC SPIRITUAL EXTRACURRICULAR ON STUDENT BEHAVIOR IN BENGKULU - Pasmah Chandra; Nelly Marhayati; Ersa Mala Aliza (Conciencia, 2020)
The study was aimed at seeing how extracurricular Islamic spirituality affects student’s behavior at SMAN 10 Bengkulu. The kind of research that was used in this study was quantitative research with a quantitative descriptive approach. The data-collection techniques used were questionnaires, observation, interview, and documentation. The sample in this study was all of the students who have participated in extracurricular Islamic Spirituality at SMAN 10 Bengkulu. Researchers used probability sampling techniques of simple random sampling. Research data analysis used simple linier regression analysis, F-Test, t-test, and coefficient determinations (R2) with the help of SPSS 16. The finding of these studies' extracurricular activities of Islamic spirituality affects student’s behavior. This was evidenced by tcount of 3,120 whereas ttable of 2,037 at a significant level of 0.05. Based on these results tcount was greater than the expectation tchart. Thus, it may be concluded that Ha was accepted and Ho was rejected so that there was an influence of Islamic spirituality extracurricular activities on student behavior by 22.8% while the remaining 77.2% was influenced by other factors not studied in this study.